On Edge Magic Total Labeling of (7, 3)-Cycle Books - Baki Swita; Ulfasari Rafflesia; Nova Henni Ms; Dolly Stio Adji; Mudin Simanihuruk (International Journal of Mathematics and Mathematical Sciences)
A graph G is called (a, b)-cycle books B[(Ca, m), (Cb, n), Pt] if G consists of m cycles Ca and n cycles Cb with a common path Pt. In this article we show that the (7, 3)-cycle books B[(C7, 1), (C3, n), P2] admits edge-magic total labeling. In addition we prove that (a, 3)-cycle books B[(Ca, 1), (C3, n), P2] admits super edge-magic total labeling for a = 7 and extends the values of a to 4x − 1 for any positive integer x. Moreover we prove that the (7, 3)-cycle books B[(C7, 2), (C3, n), P2] admits super edge-magic total labeling.